2012
DOI: 10.1002/ar.22516
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Entheses: Bridging the Gap Between Clinical and Anthropological Perspectives

Abstract: An enthesis is the interface where tendon meets bone, providing both muscle anchorage and stress dissipation. Previous anthropological research suggests size and complexity of entheses observable in osteological material, are indicative of the strain magnitude resulting from repetitive muscle contractions during the performance of daily routines. These proposed ''musculoskeletal stress markers'' are routinely incorporated into bioarcheological studies as evidence of general activity patterns past human populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
74
0
9

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(86 citation statements)
references
References 98 publications
(179 reference statements)
3
74
0
9
Order By: Relevance
“…The authors suggested that "moderate exercise" did not affect the subchondral bone volume at the enthesis, however, the tendon thickness was increased in trained rats (Frizziero et al, 2011). This raises one of the most crucial questions in the field of bone structural adaptation: what is the osteogenic potential of high intermittent stresses vs. habitual moderate stress, i.e., which type and magnitude of stress drives bone structural adaptation (Frost, 2000;Zumwalt, 2006;Ruff et al, 2006;Schlecht, 2012b)? Following this question, another arises as to whether the structural adaptation to muscle loads is different across lifespan?…”
Section: Additional Considerations For Enthesis Development Understanmentioning
confidence: 91%
See 3 more Smart Citations
“…The authors suggested that "moderate exercise" did not affect the subchondral bone volume at the enthesis, however, the tendon thickness was increased in trained rats (Frizziero et al, 2011). This raises one of the most crucial questions in the field of bone structural adaptation: what is the osteogenic potential of high intermittent stresses vs. habitual moderate stress, i.e., which type and magnitude of stress drives bone structural adaptation (Frost, 2000;Zumwalt, 2006;Ruff et al, 2006;Schlecht, 2012b)? Following this question, another arises as to whether the structural adaptation to muscle loads is different across lifespan?…”
Section: Additional Considerations For Enthesis Development Understanmentioning
confidence: 91%
“…Following this question, another arises as to whether the structural adaptation to muscle loads is different across lifespan? Does the entheseal morphology mostly reflect the activities in youth, or do the activities in advanced age also determine the appearance of attachment sites, or are both the case (Ruff et al, 2006;Schlecht, 2012b)? In that sense, it seems too simplistic to just observe the general occupation of an individual when analyzing entheses morphology, and correct interpretations may require a more precise investigation of loading activities.…”
Section: Additional Considerations For Enthesis Development Understanmentioning
confidence: 97%
See 2 more Smart Citations
“…As alternative causes for EC, inflammatory or metabolic diseases are mentioned, such as seronegative spondyloarthropathies (Resnick and Niwayama, 1995;Freemont, 2002) or diffuse idiopathic skeletal hyperostosis (DISH) (Cammisa et al, 1998;Hannallah et al, 2007;van der Merve et al, 2012). Additionally, a dependency on the type of entheses, fibrous or fibrocartilaginous (Benjamin et al, 1986(Benjamin et al, , 2002Villotte, 2006;Villotte et al, 2010;Schlecht, 2012), a stature dependency on the morphology of entheses (Zumwalt et al, 2000;Weiss, 2003Weiss, , 2004Weiss, , 2007, and particularly age dependency (Kennedy, 1989;Robb, 1998;Weiss, 2003Weiss, , 2004Weiss, , 2007Mariotti et al, 2004;Molnar, 2006;Alves Cardoso and Henderson, 2010;Villotte et al, 2010;Milella et al, 2012) are discussed in many recent articles.…”
Section: Introductionmentioning
confidence: 96%